The prototype opto-mechanical system for the Fluorescence detector Array of Single-pixel Telescopes. (4th July 2017) - Mandat, D.; Palatka, M.; Pech, M.; Schovanek, P.; Travnicek, P.; Nozka, L.; Hrabovsky, M.; Horvath, P.; Fujii, T.; Privitera, P.; Malacari, M.; Farmer, J.; et al.
Abstract: The Fluorescence detector Array of Single-pixel Telescopes is a proposed low-cost, large-area, next-generation experiment for the detection of ultrahigh-energy cosmic rays via the atmospheric fluorescence technique. The proposed design involves the deployment of several hundred large field-of-view fluorescence telescopes on a regular grid of several thousand square kilometers in ground area. This paper describes the optical design of the prototype telescope, as well as its mechanical support structure.